Some aspects of the warrior concept in the Eastern Hallstatt Circle - Potrebica, Hrvoje (Array, 1999)
The first aim of this paper is to shed some light on the process of transition from the rather levelled society of the late Bronze Age to the stratified society of the early Iron Age dominated by the clearly defined warrior aristocracy. It is very hard to identify the, so-called, Thraco-Cimmerian presence that allegedly triggered that transition. However, it can be clearly seen that some outside element strongly influenced the local population and transformed social structure introducing strong horsemen element that eventually developed in the warrior aristocracy. Analysis of grave inventories helps us to define what are distinctive features in archaeological material (especially weapons) that marks such social groups. Special consideration is given to the differences in burial ritual. The area of northern Croatia and Slovenia is also quite interesting because it is southern periphery of the Hallstatt Culture and therefore show visible influences from highly developed Mediterranean cultures (Greek and Etruscans) where warriors were central point of their social structure and had pivotal role in their world view in general. These influences are particularly visible in the sets of defence weapons that are treated as objects of prestige in Hallstatt culture and as such used in burial ritual. This paper suggest ways through which these influences reached this area and how the original concept of that material was influenced in the process of transition. Another point is how these objects were accepted and how they functioned in the context of the early Iron Age culture on this area. Although, the role of such imports within the Hallstatt Culture can be viewed from the practical point of view, it seems they are primarily objects of prestige, because the detailed analysis of grave inventories considering weapons suggest that the fighting techniques did not change, despite the introduction of the new sets of weaponry.